The impact of utilizing oyster shell soil conditioner on the growth of tomato plants and the composition of inter-root soil bacterial communities in an acidic soil environment - Zheng, Yi; Yu, Chaofan; Xiao, Yujun; Ye, Tinge; Wang, Songgang (Frontiers in Microbiology, 2024)
Introduction The objective of this study is to examine the impact of various oyster shell soil conditioners, which are primarily composed of oyster shells, on the growth of tomatoes in acidic soil. Moreover, the aim of this investigation is to analyze the variety and structure of soil bacterial populations in close proximity to tomato roots while also contributing to the understanding of the physical, chemical, and biological mechanisms of oyster shell soil conditioners. Methods Tomato plants were grown in acidic red soil in three groups: a control group and a treatment group that used two types of oyster shell soil conditioners, OS (oyster shell powder) and OSF (oyster shell powder with organic microbial fertilizer). A range of soil physicochemical properties were measured to study differences in inter-soil physicochemical parameters and the growth of tomato plantings. In addition, this study utilized the CTAB (Cetyltrimethylammonium Bromide) technique to extract DNA from the soil in order to investigate the effects of oyster shell soil conditioner on the composition and diversity of bacterial populations. Utilizing high-throughput sequencing technologies and diversity index analysis, the composition and diversity of bacterial populations in the soil adjacent to plant roots were then evaluated. Ultimately, correlation analysis was used in this study to explore the relationship between environmental factors and the relative abundance of soil bacteria in the inter-root zone of tomato plants. Results The findings indicated that the oyster shell soil conditioners were capable of modifying the physicochemical characteristics of the soil. This was evidenced by significant increases in soil total nitrogen (16.2 and 59.9%), soil total carbon (25.8 and 27.7%), pH (56.9 and 55.8%), and electrical conductivity (377.5 and 311.7%) in the OS and OSF groups, respectively, compared to the control group (p < 0.05). Additionally, data pertaining to tomato seed germination and seedling growth biomass demonstrated that both oyster shell soil conditioners facilitated the germination of tomato seeds and the growth of seedlings in an acidic red clay soil (p < 0.05). On the other hand, the application of two oyster shell soil conditioners resulted in a modest reduction in the diversity of inter-root soil bacteria in tomato plants. Specifically, the group treated with OSF exhibited the most substantial fall in the diversity index, which was 13.6% lower compared to the control group. The investigation carried out on the soil between tomato plant roots yielded findings about the identification of the ten most abundant phyla. These phyla together represented 91.00-97.64% of the overall abundance. In the inter-root soil of tomatoes, a study identified four major phyla, namely Proteobacteria, Bacteroidetes, Acidobacteria, and Actinobacteria, which collectively accounted for up to 85% of the total abundance. At the general level, the relative abundance of Massilia increased by 2.18 and 7.93%, Brevundimonas by 5.43 and 3.01%, and Lysobacter by 3.12 and 7.49% in the OS and OSF groups, respectively, compared to the control group. However, the pathogenic bacteria unidentified_Burkholderiaceae decreased by 5.76 and 5.05%, respectively. The correlation analysis yielded conclusive evidence indicating that, which involved the use of CCA (Canonical Correlation Analysis) graphs and Spearman correlation coefficients, pH exhibited a positive correlation (p < 0.05) with Shewanella and a negative correlation (p < 0.05) with Bradyrhizobium. The relative abundance of Lysobacter and Massilia exhibited a positive correlation with the levels of total soil nitrogen. Discussion The utilization of oyster shell soil conditioner on acidic red soil resulted in several positive effects. Firstly, it raised the pH level of the inter-root soil of tomato plants, which is typically acidic. This pH adjustment facilitated the germination of tomato seeds and promoted the growth of seedlings. In addition, the application of oyster shell soil conditioner resulted in changes in the structure of the bacterial community in the inter-root soil, leading to an increase in the relative abundance of Proteobacteria and Bacteroidetes and a decrease in the relative abundance of Acidobacteria. Furthermore, this treatment fostered the proliferation of genera of beneficial bacteria like Massilia, Brevundimonas, and Lysobacter, ultimately enhancing the fertility of the red soil.